Peningkatan Kapasitas Produksi Petani Jamur Tiram Desa Karangpring Melalui Teknologi Alat Pengepres Baglog Dua Tuas - Arum, Ayu Puspita; Setiyono, Setiyono; Subroto, Gatot; Muchlison, Wildan (PRIMA: Journal of Community Empowering and Services, 2022)
Increasing Production Capacity of Oyster Mushroom Farmers in Karangpring Village through Baglog Two-Level Pressing Technology. The production capacity of baglog manually by oyster mushroom farmers in Karangpring Village, Sukorambi District, Jember Regency is 1,250 baglogs/month with a low average productivity of about 625 kg/4 months which is only done by 2 workers. About 25% of the total baglog made had poor oyster mushroom mycelium growth due to the lack of density of baglog so oyster mushrooms could not be harvested. The problem that can be identified is the lack of experienced workers who can properly compact baglog from F3 oyster mushroom seeds. Oyster mushroom baglog that is less dense causes the growth of oyster mushroom mycelia to be inhibited, resulting in decreased productivity. There needs to be empowerment that aims to provide education on the technique of properly compacting the oyster mushroom baglog while at the same time providing assistance with a two-lever baglog press. The method used in this empowerment activity is training and demonstration of the use of a two-lever baglog press. The result of this service activity is that baglog pressing training is carried out with a two-lever baglog pressing machine for oyster mushroom farmers. With this tool, the baglog compaction process is faster with the right density (100%) where previously 25% of the total baglog that was compacted could not be completely compacted if done manually. The production target of F3 oyster mushroom seeds, which was originally very late, became on time with only 2 workers assisted by a two-lever baglog pressing machine. Empowerment of oyster mushroom farmers through training and the provision of a two-lever baglog press was able to increase the production of F3 oyster mushroom seedlings of 10,500 baglog per month with an increase in production efficiency of 573% compared to before using the tool.